Education, Research and the Impact of Tuition Fees: A Simple Model of the University - Peter Michaelis (Universität Augsburg, Institut für Volkswirtschaftslehre, 2004)
The present paper analyses the behaviour of a university within a neoclassical equilibrium framework. Demand for enrolments is traced back to the decision of potential students which aim at maximizing expected lifetime income. Here, the key factors are the students? preferences and abilities, the quality of education offered by the university and several external determinants like, e.g., tuition fees and differences in income between graduates and non-graduates. In turn, the behaviour of the university in terms of educational efforts and the strength of academic standards depends on the demand for enrolments, on financial resources available and on the specific objectives pursued by the university. The main emphasis is on the implications of different funding mechanism (governmental grants vs. tuition fees) in combination with different objectives pursued (maximizing enrolments vs. maximizing prestige via research output). It is shown that for given financial resources a university that aims at maximizing prestige always provides only a lower quality of education for a smaller number of students compared to a university that aims at maximizing enrolments. Moreover, the effects caused by changes in governmental grants or tuition fees are quite different depending on the university?s objectives. Yet, there is also one common feature: Irrespective of which utility function is maximized, partially substituting governmental grants by tuition fees would change neither educational efforts nor academic standards, but it would inevitably lead to decreasing enrolments. As a positive side-effect, however, the average ability of the remaining population of students would increase.
urn:nbn:de:bvb:384-opus4-537605
Keywords: A2; 330; Educational Economics; University; Tuition Fees